2022
DOI: 10.1680/jgeot.20.p.064
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing bearing capacity of shallow foundations through cement-stabilised sand layer over weakly bonded residual soil

Abstract: The addition of a soil–cement reinforcement layer is an alternative to improve the bearing capacity of shallow foundations on weak soils. Recent research with small-scale tests highlighted the influence of the soil–cement layer's geometry and tensile strength in bearing capacity prediction of footings resting on treated layers. This work presents the evaluation of field static load tests of circular steel footings resting on soil–cement layers above a weak residual soil. Results showed on the one hand that tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…During the intensive search for alternative binders to OPC, alkaline-activated cements (AAC) are rapidly gaining ground, as it involves mostly industrial wastes, and the results are competitive with those produced by OPC. Despite being a recent technique, many studies on alkali-activation of wastes have already shown several advantages of these alternative materials, from high compressive strengths, low shrinkage levels, acid and fire resistance and low thermal conductivity [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the intensive search for alternative binders to OPC, alkaline-activated cements (AAC) are rapidly gaining ground, as it involves mostly industrial wastes, and the results are competitive with those produced by OPC. Despite being a recent technique, many studies on alkali-activation of wastes have already shown several advantages of these alternative materials, from high compressive strengths, low shrinkage levels, acid and fire resistance and low thermal conductivity [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have explored the pozzolanic properties of waste glass and its application to a new variety of binders, which include the recycling of different types of industrial waste and by-products (i.e., industrial, agricultural and urban), and have gained notability as soil stabilizers in substitute to OPC in soil-cement [8,17,20,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%